Emerging tyrosine kinase inhibitors for esophageal cancer. (June 2013) - Ku, Geoffrey Y; Ilson, David H
Abstract : Introduction: Because of the poor prognosis for patients with esophagogastric cancers (EGCs), increasing attention has focused on targeted agents. Areas covered: Targets include epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), Her2, mammalian target of rapamycin (mTOR), and MET. We briefly discuss preclinical data and the rationale for targeting these pathways and summarize the results of clinical trials of tyrosine kinase inhibitors (TKIs) against these targets. Expert opinion: While anti-EGFR therapy has been extensively investigated, completed Phase III trials suggest that this is not a promising target. A Phase III trial of an anti-VEGF antibody failed to show improvement in the primary endpoint of overall survival but response rates and progression-free survival were improved; a Phase III trial of an anti-VEGF receptor 2 antibody in second-line therapy did show improved survival. As such, Phase II and III evaluations of anti-VEGF TKIs are ongoing. The only Food and Drug Administration-approved targeted therapy in EGC is trastuzumab, an anti-Her2 antibody, and the results of a Phase III evaluation of lapatinib, an anti-Her2 TKI, are awaited. Phase III evaluation of an mTOR inhibitor has been negative. Finally, MET inhibition appears to have significant clinical potential and early testing of MET TKIs is underway.